Spherosomes as models of the biological membranes in the study of the effects of alpha radiation of radon isotopes (Experimental biology, 2015)
Studied biophysics processes occurring in the membranes under the influence of alpha radiation of radon isotopes. The specific tasks of this work were: 1) unequivocal evidence of radiation damage to membrane on models of biological membranes – spherosome; 2) measurement of the phenomenon of “dose-effect”. The relevance of this work is the factthat the isotopes of radon, according to ICRP, causing 90-95% of cancer diseases, but to date remain unknown causes their formation when internal exposure of the human body by alpha radiation of radon isotopes with energies near 5.5MeV.
Keywords: spherosomes; model of the biological membranes; alpha radiation isotopes of radon; resistant membranes; “dose-effect”